PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN MATERI LISTRIK DINAMIS - Norhasanah, Siti (Vidya Karya Jurnal Kependidikan, 2013)
Problem-based learning ( PBL ) model is a learning model that uses real-world problems as a context for students to learn about critical thinking and problem solving skills, as well as a way to acquire the knowledge and the essential concepts of the subject matter. The purpose of this study was to determine whether PBL models can improve learning outcomes of 26 students in physics class XA SMAN 1 Tanta. The data were analyzed by descriptive . The results showed that in the first cycle, students learning outcomes increase on average of 12.69 % , while in the second cycle students learn to achieve an increase on average by 21.93 % and the third cycle , students achieve average improvement of learning outcomes average of 10.77 % . Thus it can be said that through the application of the PBL , the results of studying physics grade students of SMAN 1 Tanta XA can be improved.